Control of karsts caves safety in the Połom Limestome Quarry - Bednarczyk, Zbigniew; Brych, Maria; Patla, Sławomir (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2025)
The purpose of the study was to monitor the impact of mining on the structure of crystalline limestone caves, in the vicinity of a quarry in SW Poland. The scope of work included an analysis of the geological and geotechnical conditions and safety of the caves. The research included the application of MASW Multichannel Analysis of Surfaces Waves to determine rock voids, identification of geotechnical parameters and slope stability. Short-range aerial photogrammetry was used to produce maps. Seismometers and glass plates installed near and inside the caves allowed characterization of Vs paraseismic vibration velocity, acceleration, displacement and frequency. The MASW survey determined Vs velocity and limestone strength. The 48-m long survey revealed several zones with higher values of Vs and cave zone with lower values of 70–90 m/s. It allows the identification of the cave. The slope stability analysis, taking into account the results of the geophysical survey, previous research and field observations, indicates that the slope is stable. In the second part, the magnitude of vibrations was measured as a function of charge size and distance. The research was conducted to determine the parameters of safe blasting operations, detect the caves using MASW method and minimize negative impact of exploitation on the caves. A methodol-ogy for monitoring the condition of rock slopes in the vicinity of blasting sites was presented. In the conclusions, the geotechnical parameters and the stability of the quarry slope near the caves were charac-terized. It was found that the slopes are stable with factor of safety Fos > 10. Investigations confirmed that using MASW method it is possible to detect caves and strength parameters up the depth of over 20 m. It was also possible to determine the safe level of paraseismic vibration of v = 2.45 cm/s for the studied caves.
Mining Science, Vol. 32, 2025, s. 7-29
Keywords: górnictwo; geologia; geoinżynieria; quarries; control of vibrations; geotechnical engineering; geophysics; slope stability analysis